Determination of minimum secondary winding coils turns for transformer three-phase-multiphase phase number converter - Yu. V. Moskalev (Омский научный вестник)
The article has considered an approach to determining the minimum of the secondary winding coils turns of a transformer three-phase-multiphase phase number converter. Each phase of the secondary winding of the considered converter consists of three coils connected in series placed on three different rods of the magnetic circuit. In order to solve the optimization problem, the interior-point method is used. As an example, for a three-phase-five-phase converter has determined the minimum number of turns of the secondary winding, the total power consumed by the coils of the secondary winding is calculated. A vector diagram EMF of the coils of the secondary winding is constructed, explaining the formation of a symmetrical five-phase EMF system at the terminals of the secondary winding. Using the proposed approach, it is possible to design a transformer converter of the number of phases with a three-phase primary winding and a multiphase secondary winding, the number of phases of which is more than two.